Efficiency training on safety working condition in oil palm plantation / Naimullah Fareez Jamat - Jamat, Naimullah Fareez (Faculty of Plantation and Agrotechnology, 2016)
This survey study was conducted to analyse the factors where can influencing the training on safety towards rate of accident during working condition in oil palm industry. The aim of this study was to investigate the relationship between training practices towards rate of accident. The method used was questionnaire survey. The sample is needed on this questionnaire is (80 respondent) which involve were three factor independent variable such as knowledge of safety, duration of course and rate of accident at Perbadanan Perbangunan Pertanian Negeri Perak. The all questionnaire which distribute to respondent and collected then analyse by using Statistical package for Social Science (SPSS) software. The result show there is no significant relationship between knowledge of safety with training on safety and there are significant both of two independent variable like duration of course and rate of accident with training on safety. The most contributing factor towards training on safety working condition in oil palm industry is rate of accident. The second factor contribute to training on safety is duration of course and the lowest factor contributing towards training on safety is knowledge of safety. Through this study, we recommend that government agencies or private company should improve and implement programs in emphasizes as importance training on safety for increase knowledge and awareness level of workers to reduce rate of accident in workplace.